The Effect of Germination Time and Drying Time on The Functional Characteristics of Germinated Peanut Flour - Elsa Kirana Setyawati; Erminawati Erminawati; Wuryatmo A. Sidik (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
Peanut also known as groundnut is a potential food commodity with its multi-purpose, a source of high-quality protein and oil, and contain many functional compounds such as fiber, polyphenols, vitamins and minerals, there for it has good prospects on the development of food products. Peanut in the form of flour can extend the shelf life of products, minimize the beany flavor and aflatoxin content in peanuts, as well as facilitate further processing. The purpose research of this is to determine the effect of germination time, drying time effect, and combination effect between germination time and the best drying time on the functional characteristics of germinated peanut flour.This research is experimental using factorial with a completely randomized design (CRD). The germination time in 4 levels in; 24, 28, 32, and 36 h. The drying time in 3 levels; 24, 26, and 28 h. Functional characteristic variables examinade; antioxidant activity of DPPH, total phenol, water absorption capacity, oil absorption capacity, emulsion capacity, and solubility. germination time had a significant effect on the functional characteristics of germination peanut flour; increasing (antioxidant activity, total phenol, water absorption capacity, emulsion capacity, and solubility), and decreasing oil absorption capacity. Meanwhile drying time had a significant effect; increasing (antioxidant activity, total phenol, water absorption capacity) and decreasing oil absorption capacity only. The best treatment in this research was a germinated peanut flour formulated in 36h of germination time and 26h of drying time (K4P2) with 46.43% of antioxidant activity, 0.885 mg GAE/g of total phenol, 85.67% of water absorption capacity, 85% of oil absorption capacity, 61.24% of emulsion capacity, and 22.67% of solubility. This study shows that germination and drying is a good method to improve the functional properties of germinated peanut flour.